Aging and regional productivity growth in Germany - Eckhardt Bode; Dirk Dohse; Ulrich Stolzenburg (Review of Regional Research, 2023)
We investigate the effects of aging on regional productivity growth, the mechanisms and the strength of which are not well-understood. We focus on two different manifestations of population aging—workforce aging and an increasing share of retirees—and investigate channels through which aging may impact on regional productivity growth for a~panel of German counties 2000–2019. We find that workforce aging is more negatively associated with productivity growth in urban than in nonurban regions. A~likely reason is that aging is detrimental to innovative and knowledge-intensive activities, which are heavily concentrated in cities. We also find a~negative association between the share of the retired population and productivity growth in regions with a~small household services sector. A~likely reason is that older people's disproportionate demand for local household services (including health care, recreation) requires a~re-allocation of resources from more productive manufacturing or business services to less productive household services. Regions specialized more in highly productive industries have more to lose in this process.
Keywords: E24; J11; J24; J26; R11; 330; Workforce aging; Population aging; Productivity growth; Regional analysis; Germany